Maternal knowledge about healthy eating and nutritional status in preschool children - Tarazona Rueda, Gianella Del Pilar (2022)
Introduction. Child nutrition is fully based on the competence of parents; therefore, their knowledge is of vital importance for the correct and balanced preparation of the food that their children provide. Objective. To determine if there is a relationship between maternal knowledge about healthy eating and nutritional status in preschool children of an educational institution in Metropolitan Lima, 2019. Methods. Observational, analytical - correlational and prospective research, with a sample of 132 mothers of preschool children. Spearman’s correlation analysis was performed. Results. The 47% of mothers showed a good level of knowledge about healthy eating. Among children aged 3 to 5 years, 94.4% presented normal weight-for-age (WFA), 88.2% normal weight-for-height (WFH), and 94.4% normal height-for-age (HFA). Furthermore, there is a weak inverse significant correlation between the level of knowledge and the WFA (p = 0.015, Rho = -0.327), as with the WFH (p = 0.003, Rho = -0.397). Among children older than 5 years, 92.3% showed normal HFA and 56.4% had normal BMI for age; Furthermore, there is a weak direct significant correlation between the level of knowledge and the HFA (p = 0.025, Rho = 0.253), and a weak inverse significant correlation with the BMI for age (p = 0.016, Rho = -0.273). Conclusion. The level of maternal knowledge about healthy eating shows a significant and inverse relationship with the weight-for-age and weight-for-height in children aged 3 to 5 years, and with the BMI for age in children older than 5 years, in addition to a direct relationship with the height-for-age in children older than 5 years.